Efficacy of folic acid therapy for the association between high serum vitamin B12 level with all cause mortality among hypertensive population: the CSPPT randomized clinical trial post-hoc analysis. (14th October 2021) - Cao, T; Huang, X; Huang, X; Wang, B Y; Wang, B Y; Wu, H Y; Wu, H Y; Spence, D; Spence, D; Yong, H Y; Yong, H; Cheng, X S; et al.
Abstract: Background: While higher vitamin B12 level was found to be co-related with mortality in various population, the effectiveness of folic acid therapy for this association remained unknown. Purpose: 1: Explore the association between high B12 level and all cause mortality in hypertensive population. 2: To test the primary hypothesis that therapy with enalapril and folic acid is more effective in reducing all cause mortality than enalapril alone among targeted population. Methods: Current study used post hoc analysis to examin data from the china stroke primary prevention trial (CSPPT), a randomized, double-blind, multi-center clinical trial. After excluded those lack of vitamin B12 data and with extreme B12 value, 20, 204 participants (mean age 60 [SD. 8.54]; 59.16% male gender; total mean serum vitamin B12 level 410.51 [SD. 124.85] pg/ml) were included in present study.10, 093 participants were treated with enalpril alone and 10, 111 patients took the combine use of enalapril and folic acid. The primary outcome was all cause mortality, which collected based on hospital issued death certificate and investigation during follow up period. Results: Over the medium follow-up time of 4.5 years, 308 death occurred in enalapril group and 295 death happened in enalapril-folic acid group. Differences were observed regarding sex, center, smoking & drinking status at baseline. In enalapril group, high vitamin B12 level presented positive linear association with all cause mortality and was found to be significantly differences (P=0.018). Whereas no association between high vitamin B12 level and all cause mortality were observed in enalapril and folic acid group. (P=0.448). KM curves and tertile analysis of vitamin B12 level also showed same finding. Sensitivity analysis were processed to ensure the accuracy of the study result. Conclusion: The present study not only explored that higher vitamin B12 level will increase all cause mortality in hypertensive population, but also found that high vitamin B12 level loses its co-relationship with all cause mortality after folic acid therapy, which potentially reflected the benefits of long-term, low-dose folic acid supplementation. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Key R&D Projects, Jiangxi National Key Research and Development Program